Clinker, pumice, scoria, or paralava? Vesicular artifacts of the lower Missouri basin - Estes, Mark B.; Ritterbush, Lauren W.; Nicolaysen, Kirsten (My University, 2010)
Abrading artifacts made of vesicular (porous) rock are not uncommon at archaeological sites along the Missouri River and adjacent areas. Various terms have been used to describe this material including pumice, scoria, clinker, and floatstone. Each of these terms implies different geologic origins (volcanic vs. non-volcanic) and affects interpretation of the potential modes of transport. Identification of the source area of these materials may provide significant information regarding past human movements and activities. This study focuses on vesicular artifacts in the central Plains and in particular from the Leary site (25RH1) in the southeastern corner of Nebraska. Scanning Electron Microscopy (SEM) was used to identify the chemical compositions of a subset of the Leary artifacts and comparative geologic samples of volcanic and metasedimentary origin. The results imply that the Leary (and likely many other) vesicular artifacts from the central Plains are non-volcanic in origin. The raw material from which these artifacts were made is more properly termed "paralava" and derives from outcrops in the northern Plains. Historical documents suggest that this buoyant material was transported naturally be the Missouri River as "floatstone".
Keywords: Paralava; Clinker; Scanning electron microscope; Semiquantitative analysis; Abrading artifacts